A Case of Advanced Gastric Cancer with Poor Performance Status Which Improved by Chemotherapy - Kohei Shitara; Daisuke Takahari (Case Reports in Oncology, 2010)
Introduction: The prognosis of advanced gastric cancer patients, especially those with poor performance status (PS), is generally dismally poor. Patients with PS 3–4 are usually ineligible for participation in clinical studies and are managed with only best supportive care. Case Report: A 63-year-old male with advanced gastric cancer was admitted to our hospital. His PS was markedly impaired (Eastern Cooperative Oncology Group PS 4), with dyspnea secondary to lymphangitis, pleuritis and pericarditis). He also had bilateral leg paralysis due to multiple bone metastases. He was treated with chemotherapy using 5-fluorouracil and leucovorin for 14 days with pericardial drainage followed by intrapericardial infusion of cisplatin. He was also treated with radiotherapy for bone metastasis. The patient required 5 l/min oxygen therapy at the start of chemotherapy, but his dyspnea was improved by day 14 and he no longer required supplemental oxygen therapy. His leg paralysis also improved with the radiation therapy. His PS was significantly improved with this multimodal treatment modality, and he was ultimately discharged with chemotherapy with oral fluoropyrimidine. Conclusion: This case suggests that multimodal therapy including chemotherapy may be beneficial in advanced gastric cancer patients even in the setting of poor PS. Further study might be required to confirm the benefit of chemotherapy in this patient population.